An Underactuated Drift-Free Left Invariant Control System on a Specific Lie Group - Camelia Pop Arieşanu (Journal of Applied Mathematics)
The paper presents a geometrical overview on an optimal control problem on a special Lie group. The Hamilton-Poisson realization of the dynamics offers us the possibility to study the system from mechanical geometry point of view.